Proceedings of the Twenty-Ninth Annual ACM-SIAM Symposium on Discrete Algorithms 2018
DOI: 10.1137/1.9781611975031.146
|View full text |Cite
|
Sign up to set email alerts
|

On Simultaneous Two-player Combinatorial Auctions

Abstract: We consider the following communication problem: Alice and Bob each have some valuation functions v 1 (·) and v 2 (·) over subsets of m items, and their goal is to partition the items into S,S in a way that maximizes the welfare, v 1 (S)+v 2 (S). We study both the allocation problem, which asks for a welfare-maximizing partition and the decision problem, which asks whether or not there exists a partition guaranteeing certain welfare, for binary XOS valuations. For interactive protocols with poly(m) communicati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
42
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(42 citation statements)
references
References 50 publications
0
42
0
Order By: Relevance
“…This problem is provably easier than finding an approximate allocation in the interactive setting: any r-round protocol for finding an approximate allocation can be used to obtain an (r + 1)-round protocol for estimating the value of social welfare with O(n) additional communication; simply compute the approximate allocation in the first r rounds and spend one additional round in which each player declares her value for the assigned bundle to the referee. It was shown very recently in [6] that this loss of one round in the reduction is unavoidable (see Section 3 for further details). However, this extra one round is essentially negligible for our purpose as we are interested in the asymptotic dependence of the approximation ratio and the number of rounds.…”
Section: Communication Modelmentioning
confidence: 99%
“…This problem is provably easier than finding an approximate allocation in the interactive setting: any r-round protocol for finding an approximate allocation can be used to obtain an (r + 1)-round protocol for estimating the value of social welfare with O(n) additional communication; simply compute the approximate allocation in the first r rounds and spend one additional round in which each player declares her value for the assigned bundle to the referee. It was shown very recently in [6] that this loss of one round in the reduction is unavoidable (see Section 3 for further details). However, this extra one round is essentially negligible for our purpose as we are interested in the asymptotic dependence of the approximation ratio and the number of rounds.…”
Section: Communication Modelmentioning
confidence: 99%
“…More formally, a δ-error α-approximation protocol needs to, for each input instance I sampled from D, output a number in the range [ This problem is provably easier than finding an approximate allocation in the interactive setting: any r-round protocol for finding an approximate allocation can be used to obtain an (r + 1)-round protocol for estimating the value of social welfare with O(n) additional communication; simply compute the approximate allocation in the first r rounds and spend one additional round in which each player declares her value for the assigned bundle to the referee. It was shown very recently in [6] that this loss of one round in the reduction is unavoidable (see Section 3 for further details). However, this extra one round is essentially negligible for our purpose as we are interested in the asymptotic dependence of the approximation ratio and the number of rounds.…”
Section: Communication Modelmentioning
confidence: 99%
“…The reason is that while the problem of estimating the social welfare is provably easier than the problem of finding an approximate allocation, the reduction requires one additional round of interaction and hence, in general, a simultaneous protocol for the problem of finding the allocation only implies a 2-round (and not a simultaneous) protocol for the social welfare estimation problem 3 . Interestingly, for the case of n = 2 players, Braverman et al [6] very recently showed that the problem of estimating the social welfare is indeed provably harder than finding an approximate allocation for simultaneous protocols. In the light of this result, it seems plausible that one can indeed improve the protocol of [9] and find an O(m 1/4 )-approximation protocol for finding an approximate allocation (matching the lower bound of [9]); however, Theorem 1 suggests that if such a protocol exists, it necessarily should be oblivious to the welfare of the allocation it provides.…”
Section: Warm Up: a Lower Bound For Simultaneous Protocolsmentioning
confidence: 99%
See 1 more Smart Citation
“…This has led the researchers to study the communication complexity of this problem that can capture arbitrary queries to valuations [3-5, 12-14, 18, 22, 36, 37]. Although a clear path for proving a separation between the communication complexity of truthful mechanisms and general algorithms was shown recently in [12] (see also [5,22]), no such separation is still known.…”
Section: Introductionmentioning
confidence: 99%